Մասրենու CO2-լուծազատվածքի ելքն ըստ հումքի մանրացման աստիճանի և կիրառումը հրուշակեղենի արտադրությունում - Պետրոսյան, Ա. Ա. (ՀԱԱՀ հիմնադրամ)
Հրուշակեղենի արտադրության ծավալների ավելացումը և տեսականու ընդլայնումը պայմանավորված են նոր հումքատեսակների կիրառման տեխնոլոգիաների մշակմամբ և արտադրատեսակների արտադրությամբ: Հետազոտությունների համաձայն՝ որպես բուժկանխարգելիչ հումքատեսակ կարող է օգտագործվել մասրենին: Վերջինիս CO2-լուծազատման ռեժիմային պարամետրերի մաթեմատիկական մոդելի մշակմամբ ապացուցվել է նոր սարքավորման կիրառման և լուծազատման արդյունավետությունը։ Увеличение объемов производства и расширение ассортимента кондитерских изделий обусловлены разработкой технологий использования нового сырья и производством новых видов продукции. Согласно исследованиям, сырьем для производства лечебно-профилактического экстракта может послужить шиповник. В результате разработки математической модели параметров режима CO2-экстракции доказана эффективность процесса экстракции и использования нового оборудования. The increase of confectionery production volumes and expansion of product range are related to the development of technologies for new raw materials application and to the wide product range manufacture. According to the conducted investigations the rose-hip can be applied as a preventive and curative raw material. Upon the development of the mathematical model for rose-hip CO2 extraction regime parameters, the efficiency of new equipment application and extraction process has been proved. According to the conducted experiments, the maximum yield of carotenoid pigments in the solution is ensured at a relatively lower temperature of the solution. Therefore, the task was set to identify two dependencies: the yield of CO2-solution and the yield of the total amount of carotenoid pigments in that solution depending on the duration and temperature of the process. The optimal parameters of the dissolution process have been determined by the mathematical planning method. As a result of the mathematical modeling of the technological process of CO2-dissolution, it has been found out that the yield of the solution within the studied ultrasound frequencies ranges from 1.0-1.2, while the content of carotenoids in the solution is within 90-91.5 %. Moreover, it has been found out that the maximum values of the mentioned outputs are obtained at temperatures of +15...+22 0C. Thus, according to the research results, sweet brier (rose hips) can be used as a preventive medicine.
Keywords: Սննդագիտություն և տեխնոլոգիա